Development Job Sheet Based Performance Assessment to Improve Skills Overhaul Toyota Transmission in Vocational High Schools - Sigit Purnomo; Ade Listanto; Samidjo Samidjo; Muhammad Hakiki; Dwi Susanto (VANOS Journal of Mechanical Engineering Education, 2024)
This research and development aims to: 1) the development of performance assessment based job sheets to improve manual transmission overhaul skills, 2) the feasibility of performance assessment based job sheets to improve manual transmission overhaul skills and 3) students' responses to the development of performance assessment based job sheets to improve skills manual transmission overhaul. The development model used in this research uses the Four-D model which consists of 4 stages, namely define, design, development and disseminate. The results of this research and development show that the feasibility level of media experts is 87.33% (very feasible) and material experts are 91.01% (very feasible). The small-scale trial got a result of 93.44% (strongly agree) and the limited scale trial got a percentage of 94.97% (strongly agree). Based on the results of this research, it can be concluded that job sheets are suitable for use for learning.